Predisposing factors and effects of fetal bradycardia following cordocentesis at mid-pregnancy - Wanapirak C. (2014)
Objectives: To identify predisposing factors of fetal bradycardia following cordocentesis at mid-pregnancy and to compare the pregnancy outcomes to those without bradycardia. Methods: All cordocenteses performed at 1822 weeks of gestation were prospectively enrolled. The inclusion criteria consisted of: (i) singleton pregnancies; (ii) no fetal structural or chromosomal abnormalities; (iii) the procedures done by experienced operators. They were divided into two groups; procedures with fetal bradycardia (Group 1) and those without bradycardia (Group 2). Factors related to bradycardia were identified and pregnancy outcomes between the two groups were also compared. Results: Of 6147 cordocenteses recruited, 2829 met the inclusion criteria. Of these,152 had fetal bradycardia whereas the remaining 2677 did not. The procedures involving placenta penetration, and umbilical cord bleeding were significantly related to a higher rate of fetal bradycardia. On the other hand, cordocenteses with fetal bradycardia had a significantly higher rate of fetal loss (11.8 vs. 1.9%, respectively, p = 0.001) as well as a higher rate of low birth weight and preterm birth. Conclusions: Cordocentesis with placenta penetration and umbilical cord bleeding carries a higher risk for fetal bradycardia and fetal bradycardia was an independent factor for a higher rate of fetal loss, preterm birth and low birth weight. © 2012 Informa UK, Ltd.